STAT1 signaling modulates HIV-1–induced inflammatory responses and leukocyte transmigration across the blood-brain barrier - Chaudhuri, Anathbandhu (American Society of Hematology, 2008)
The relationship among neuroinflammation, blood-brain barrier (BBB) dysfunction, and progressive HIV-1 infection as they affect the onset and development of neuroAIDS is incompletely understood. One possible link is signal transducers and activators of transcription (STATs) pathways. These respond to proinflammatory and regulatory factors and could affect neuroinflammatory responses induced from infected cells and disease-affected brain tissue. Our previous works demonstrated that HIV-1 activates pro-inflammatory and interferon-alpha–inducible genes in human brain microvascular endothelial cells (HBMECs) and that these genes are linked to the Janus kinase (JAK)/STAT pathway. We now demonstrate that HIV-1 activates STAT1, induces IL-6 expression, and diminishes expression of claudin-5, ZO-1, and ZO-2 in HBMECs. The STAT1 inhibitor, fludarabine, blocked HIV-1–induced IL-6, diminished HIV-1–induced claudin-5 and ZO-1 down-regulation, and blocked HIV-1– and IL-6–induced monocyte migration across a BBB model. Enhanced expression and activation of STAT1 and decreased claudin-5 were observed in microvessels from autopsied brains of patients with HIV-1–associated dementia. These data support the notion that STAT1 plays an integral role in HIV-1–induced BBB damage and is relevant to viral neuropathogenesis. Inhibition of STAT1 activation could provide a unique therapeutic strategy to attenuate HIV-1–induced BBB compromise and as such improve clinical outcomes.